The Effect of Teaching Using Preferred Learning Styles on Students’ Performance, in Biology and Geography in Secondary Schools in Nairobi County, Kenya - Kaitho, Simon Sila; Kiptiony, Gladys Jerobon; Ngumi, Owen (KABARAK UNIVERSITY, 2018)
In Nairobi County, students in both private and public schools have not been performing satisfactorily in sciences. A study therefore was done to establish the effect of matching of teaching styles with preferred leaning styles of students’ performance in biology and geography. Multivariate analysis of variance in geography F (1, 1315) = 2870.1, p = .000) and in biology F (1, 1315) = 2994.1, p = .000), and linear regression in geography, F (1, 1315) = 2870.056, p = .000, and in biology, F (1, 1315) = 2994.137, p = .000analysis showed statistically significant effect on performance of students taught using preferred learning styles. The findings lead to a conclusion that there is a need to inform teachers to identify, and teach their learners according to the learners’ preferred learning styles to enhance their performance in sciences.
FULL TEXT
Keywords: Preferred Learning Styles, Biology, Geography, Teaching